Identification of mutations in circulating cell-free tumour DNA as a biomarker in hepatocellular carcinoma. (July 2019) - Howell, Jessica; Atkinson, Stephen R.; Pinato, David J.; Knapp, Susanne; Ward, Caroline; Minisini, Rosalba; Burlone, Michela E.; Leutner, Monica; Pirisi, Mario; Büttner, Reinhard; Khan, Shahid A.; Thursz, Mark; et al.
Abstract: Background: Hepatocellular carcinoma (HCC) is increasing globally. Prognostic biomarkers are urgently needed to guide treatment and reduce mortality. Tumour-derived circulating cell-free DNA (ctDNA) is a novel, minimally invasive means of determining genetic alterations in cancer. We evaluate the accuracy of ctDNA as a biomarker in HCC. Methods: Plasma cell-free DNA, matched germline DNA and HCC tissue DNA were isolated from patients with HCC (n = 51) and liver cirrhosis (n = 10). Targeted, multiplex polymerase chain reaction ultra-deep sequencing was performed using a liver cancer–specific primer panel for genes ARID1A, ARID2, AXIN1, ATM, CTNNB1, HNF1A and TP53 . Concordance of mutations in plasma ctDNA and HCC tissue DNA was determined, and associations with clinical outcomes were analysed. Results: Plasma cell-free DNA was detected in all samples. Lower plasma cell-free DNA levels were seen in Barcelona Clinic Liver Cancer (BCLC A compared with BCLC stage B/C/D (median concentration 122.89 ng/mL versus 168.21 ng/mL, p = 0.041). 29 mutations in the eight genes (21 unique mutations) were detected in 18/51 patients (35%), median 1.5 mutations per patient (interquartile range 1–2). Mutations were most frequently detected in ARID1A (11.7%), followed by CTNNB1 (7.8%) and TP53 (7.8%). In patients with matched tissue DNA, all mutations detected in plasma ctDNA detected were confirmed in HCC DNA; however, 71% of patients had mutations identified in HCC tissue DNA that were not detected in matched ctDNA. Conclusion: ctDNA is quantifiable across all HCC stages and allows detection of mutations in key driver genes of hepatic carcinogenesis. This study demonstrates high specificity but low sensitivity of plasma ctDNA for detecting mutations in matched HCC tissue. Highlights: Tumour-derived circulating cell-free DNA (ctDNA) can be detected in patients with hepatocellular cancer. Levels of ctDNA correlate with disease stage, such that levels increased with worsening tumour stage. Mutations in key known drivers of carcinogenesis were identified in ctDNA. All mutations in ctDNA were found in matched tumour tissue.